Telomere length as a marker of changes in body composition and fractures-an analysis of data from the NHANES 2001-2002 - Guo, Youfeng; Zhao, Haihong; Wang, Feng; Xu, Haowei; Liu, Xiaowei; Hu, Tao; Wu, Desheng (Frontiers in Immunology, 2023)
Purpose: There has been an association between changes in body composition, fracture incidence, and age in previous studies. Telomere length (TL) has been proposed as a biomarker of aging. However, the relationship between body composition, fractures, and TL has rarely been studied. Therefore, this study aimed to investigate the correlation between TL and body composition and fractures. Patients and methods: 20950 participants from the 2001-2002 National Health and Nutrition Examination Survey (NHANES) were included in the final analysis. In NHANES, body compositions were measured with DXA, and TL was determined with quantitative PCR. Correlation analysis of TL and body composition was conducted using multivariate weighted linear regression and logistic regression models.Results: The results showed that TL positively correlated with bone mineral density (BMD) and bone mineral content (BMC) in most body parts. However, BMD and BMC were negatively connected with TL in the upper limbs and skull. Fat content was negatively associated with TL, while muscle content was positively linked to TL. In addition, TL's trend analysis results were consistent with the regression model when transformed from a continuous to a classified variable.An increase in TL was associated with a higher incidence of wrist fractures, while a decrease in spine fractures. The above correlation also has a certain degree of sex specificity.Our study indicate that TL is associated with body composition as well as fractures, but further research is needed to confirm these contrasting associations in the skull, upper limbs, and wrists.